How apps impact farming communities [in Kenya] - Wangari Mutiga, Mary; Ndogo Ndung'u, Simon; Mwangi Thiga, Moses (Technical Centre for Agricultural and Rural Cooperation, 2014)
The success of mobile applications in the agricultural sector has been largely measured in terms of numbers, but what has the impact of these apps been on communities as a whole?